APPROPRIATE LABORATORY AND IMAGING APPROACH FOR EARLY DIAGNOSIS IN HOSPITAL SETTING - Teguh Kristian Perdamaian (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
The main objective of global health is to reduce preventable death equally throughout the world. One important strategy is primary prevention through health promotion and early detection. Early diagnosis is defined as several methods to determine in patients the nature of a disease or disorder at its early stage of progression. In a referral health system, such as Indonesia, early diagnosis could be implemented both in primary care and secondary or tertiary referral hospital. Primary care centres screens fatal diseases, such as cancer and cardiovascular risk factors, mostly in asymptomatic patients with identified risk of having the diseases. Accordingly, the early detection programme has been designed for large population in a community setting. It is uncommon for hospitals in Indonesia applying primary prevention where most of the patients are referred with at least a couple of differential diagnoses. Subsequently, early diagnosis in hospital setting would be defined either as accelerating the diagnosis confirmation or detecting any uncommon findings on patients with atypical presentation. In some situation, early detection of life-threatening condition at hospital would prolong or even prevent death. Aside from accurate history taking and comprehensive physical examination, advance laboratory procedure and imaging might assist in early detection at hospital setting. This time, our issue presents case reports on the benefit of early detection in the management of rare disease, anaemia, and COVID-19 pandemic among patients without symptoms or with atypical presentation. In developed countries, most of known congenital diseases were screened prenatally or immediately after delivery. The most common practice in Indonesia is a regular prenatal ultrasound and through physical examination of the baby in their first week. However, this approach would still miss many rare diseases with delayed presentation such as Legg-Calve-Perthes Diseases (LCPD). Pradyana and Astuti1 discussed a paediatric case of LCPD highlighting the difficulty in diagnosis confirmation on a limp gait symptom. Serial imaging not only important in case follow-up, but also to detect newly existing abnormalities which verify the presence of LCPD. Iron deficiency anaemia (IDA) primarily affects women and children in Indonesia. Currently, school-based screening of haemoglobin in teenage girls could prevent the sequalae of IDA through iron supplementation. Early detection in anaemia would determine the presence of IDA before the declined haemoglobin. Recently, international investigators discovered novel biomarker to detect the presence of IDA in asymptomatic patients. Fenty described the potential of using reticulocyte haemoglobin equivalent (Ret-He) to characterize IDA amongst asymptomatic patients in hospital settings.2 This approach would be beneficial for screening purpose in high-risk population, both in community and hospital setting. During COVID-19 pandemic, early diagnosis is a necessity to reduce the infection rate with early quarantine. However, challenging situation might come in patients with atypical presentation, such as gastritis. Widiastana et al describe the later COVID positive result on patients with gastritis which nonresponsive to general treatment.2 The patients did not have any classical signs and symptoms of COVID-19, hence in the community, misdiagnosis of similar condition might exacerbate the rising infection cases.